Dampak Implementasi Insentif dan Jaminan Sosial Membantu Meningkatksan Produktivitas Kerja Karyawan Pada UD Kembang Batu Lestari di Mengwi Badung - Ni Putu Sri Mariyatni; I Made Setena (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
This study aims to determine the impact of the implementation of incentives and social security programs to help increase employee productivity. This research was conducted at UD Kembang Batu Lestari in Mengwi Badung. The population in this study were 35 employees of UD Kembang Batu Lestari, the method of determining the sample using the census method that all employees became respondents. The analysis technique used is multiple linear regression analysis. The results of multiple linear regression analysis Y = 0.603 + 0.400X1 + 0.515X2. This means that the increase in employee work productivity is influenced by the increase in incentives and social security together. The F-test is a test of the significance of multiple linear regression coefficients obtained by F-count 83.262> F-table 3.23, indicating that there is indeed a significant effect simultaneously. between incentives and guarantees of employee work productivity. The significance test using the t-test obtained the t-value for the incentive and social security variables, respectively 2.747 and 4.157> t-table 1.684, indicating that it is true that there is a positive and partially significant effect between incentives and social security on work productivity employees.